Experimental investigation of hydrogen adsorption in doped silicon-carbide nanotubes. (5th January 2016) - Barghi, Seyed Hamed; Tsotsis, Theodore T.; Sahimi, Muhammad
Abstract: Silicon-carbide nanotubes were synthesized by the reaction between SiO vapor as the Si source and carbon nanotubes as the carbon precursor. The resulting nanotubes were then purified with a hot, concentrated NaOH solution in order to remove the amorphous silica from their surface. The purified silicon-carbide nanotubes were doped with either potassium (K) or titanium (Ti). The hydrogen adsorption isotherms of the nanotubes were measured gravimetrically with the aid of a magnetic suspension microbalance. The results indicate that the K-doped silicon-carbide nanotubes exhibit promise as a hydrogen adsorption material, storing three times more hydrogen than the carbon nanotubes. Highlights: Pure SiCNTs were synthesized using a gas/solid reaction. The SiCNTs were doped with titanium (Ti). The SiCNTs were doped with Potassium (K). Hydrogen uptake capacity of the pure and doped SiCNTs was gravimetrically measured.